To compare trans-vaginal ultrasound colour doppler (TUCD) with hysteroscopy and guided endometrial biopsy in diagnosing abnormal uterine bleeding - Choudhary, Swati; Ahmad, Syed Nawaz; Agarwal, Shefali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To compare trans-vaginal ultrasound Colour Doppler (TUCD) with hysteroscopy and guided endometrial biopsy in diagnosing abnormal uterine bleeding. Methods: A total of 50 consecutive and haemodynamically stable patients aged more than 40 years with abnormal uterine bleeding (AUB) were included in the study. Patients with pregnancy and probable cervical malignancy were excluded. All the patients were subjected to TUCD followed by hysteroscopic directed endometrial biopsy during the follicular phase of the menstrual cycle between 7th and 11th day to diagnose the underlying pathology. In postmenopausal female both TUCD and hysteroscopy were performed on any day. Results of both the procedures were compared. Results: The sensitivity and specificity of TUCD as compared to hysteroscopy in diagnosing polyp was found out to be 27.78% and 100%; for fibroid 100% and 84.4%; for endometrial hyperplasia 86.36% and 96.43%; for endometrial carcinoma 71.43% and 100%; and for endometrial atrophy 100% and 100%, respectively. After application of kappa statistics, the degree of agreement between the two diagnostic procedures was found to be 0.599 which was considered to be good. Conclusions: Conditions like fibroid, endometrial atrophy and cases of A-V malformation are better diagnosed with TUCD, while others like endometrial polyps, endometrial carcinoma are better detected on hysteroscopy. TUCD can diagnose most of the pathologies but not all, so it can be used as an adjunct to hysteroscopy to diagnose endometrial pathology, but can surely not replace hysteroscopy.